Temporal Differential Proteomes of Clostridium difficile in the Pig Ileal-Ligated Loop Model - Janvilisri, Tavan (Public Library of Science, 2012)
The impact of Clostridium difficile infection (CDI) on healthcare is becoming increasingly recognized as it represents a major cause of nosocomial diarrhea. A rising number of CDI cases and outbreaks have been reported worldwide. Here, we developed the pig ileal-ligated loop model for semi-quantitative analysis comparing temporal differential proteomes in C. difficile following in vivo incubation with in vitro growth using isobaric tags for relative and absolute quantification (iTRAQ). Proteins retrieved from the in vitro cultures and the loop contents after 4, 8, and 12 h in vivo incubation were subjected to in-solution digestion, iTRAQ labeling, two-dimensional liquid chromatography/tandem mass spectrometry and statistical analyses. From a total of 1152 distinct proteins identified in this study, 705 proteins were available for quantitative measures at all time points in both biological and technical replicates; 109 proteins were found to be differentially expressed. With analysis of clusters of orthologous group and protein-protein network interactions, we identified the proteins that might play roles in adaptive responses to the host environment, hence enhancing pathogenicity during CDI. This report represents the quantitative proteomic analysis of C. difficile that demonstrates time-dependent protein expression changes under conditions that mimic in vivo infection and identifies potential candidates for diagnostic or therapeutic measures.